The prodromal phase of obesity-related chronic kidney disease: early alterations in cardiovascular and renal function in obese children and adolescents - Doyon, Anke; Schaefer, Franz (Nephrology, dialysis, transplantation, 2013)
Childhood overweight and obesity is a relevant health condition with multi-organ involvement. Obesity shows significant tracking into adult life and is associated with an increased risk of serious adverse health outcomes both during childhood and later adulthood. The classical sequelae of obesity such as hypertension, metabolic syndrome and inflammation do develop at a paediatric age. Cardiovascular consequences, such as increased carotid intima-media thickness, and left ventricular hypertrophy, as well as functional alterations of the heart and arteries, are commonly traceable at an early age. Renal involvement can occur at a young age and is associated with a high probability of progressive chronic kidney disease. There is solid evidence suggesting that consequent treatment including both lifestyle changes and pharmacological therapy can reduce cardiovascular, metabolic and renal risks in obese children and adolescents.
Gesehen am 18.12.2020